ANALYSIS OF MARINE BIODIVERSITY AS UNDERWATER MACRO PHOTOGRAPHY (UMP) TOURISM OBJECTS IN TULAMBEN WATERS, BALI (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Resources (marine biota) on Underwater Macro Photography (UMP) special interest diving tours are used as commodity objects. The potential of resources for UMP dive tourism needs to be explored as a special attraction in diving tourism, especially in the character of the environment that does not have a coral reef ecosystem that is so tight. The aim of the research is to analyze the diversity, the frequency of occurrence of species, and diversity in the marine reserved in Tulamben to bring up the potential of UMP tourism resources. The study was conducted in March-August 2018 and observations were made on 6 stations in two depths using belt transects. The results showed that the UMP species in all stations was 92 species from 60 genera and they can be divided into 7 categories of marine biota. The location of the highest diversity of genera is in Singkil with 20 genera. The most frequency of appearance of biota is in the nudibranch, fish and shrimp category. Diversity of species in each site/120m2 falls in  to the medium category. The Coral Garden location of all stations has the lowest value of various biota categories due to the high diving activities which have an impact on environmental damage and can disrupt the life of the biota at this location.